Isolation and Quantification of Plant Extracellular Vesicles - Brian Rutter; Katie Rutter; Roger Innes (Bio-Protocol, 2017)
Extracellular vesicles (EVs) play an important role in intercellular communication by transporting proteins and RNA. While plant cells secrete EVs, they have only recently been isolated and questions regarding their biogenesis, release, uptake and function remain unanswered. Here, we present a detailed protocol for isolating EVs from the apoplastic wash of Arabidopsis thaliana leaves. The isolated EVs can be quantified using a fluorometric dye to assess total membrane content.